The Effective of Radiofrequency Ablation of Pulmonary Veins by the Patients with Persistent Atrial Fibrillation - D. D., Kandlbekov; Kh. N., Kodirov.; G. I., Kodirova; B. A., Avazbekov (European Journal of Life Safety and Stability (2660-9630), 2022)
To decide the adequacy of radiofrequency removal (RFA) with concomitant Coronary Supply route Bypass Joining (CABG) by the patients with tireless atrial fibrillation (AF) depending on the glomerular filtration rate (GFR). It was appeared that the nearness of renal brokenness in patients with determined AF antagonistically impacts on viability of RFA with concomitant CABG and a brief- and long-term cardiovascular forecast.